FILSAFAT HUKUM PIDANA PADA ANAK DI IRAN DAN INDONESIA - Sandya Sandya Mahendra; Bambang Sukoco; Moh. Indra Bangsawan (Academic Journal of Islamic Principles and Philosophy, 2022)
Every child has human rights as well as the rights of adults, so respecting children's rights is the same as respecting human rights. This paper aims to compare the policy of imposing the death penalty on a child between Iran and Indonesia. This research is a normative legal research conducted by examining library materials or secondary data. The approach used is a comparative approach, which is to compare child protection laws between Iran and Indonesia. The regulation of criminal penalties against children in Iran is regulated in Article 91 of the Iranian Islamic Criminal Code in 2013 and in Indonesia it is regulated in Law Number 35 of 2014 concerning Child Protection and Law Number 11 of 2012 concerning the Child Criminal Justice System. The regulation of legal protection for children in Iran and in the State of Indonesia, when compared, has quite basic differences in several aspects of the provisions of criminal acts and the criminal system. In the criminal setting in Iran, it justifies the application of the death penalty for crimes committed by children under 18 years of age. In the last 7 years, almost all juvenile offenders who were executed were sentenced to death based on qisas and hudud verses. Meanwhile, in Indonesia, it does not apply the death penalty to children but prioritizes restorative justice and diversion which is intended to avoid and keep children away from the judicial process so as to avoid stigmatization of children in conflict with the law and it is hoped that children can return to the social environment naturally.